FAMILY SUPPORT IS CRUCIAL FOR DIALYSIS PATIENTS COMPLIANCE TO TREATMENT AND QUALITY OF LIFE - Milenkova, M; Trajcheska, L; Mladenovska, D; Blerim, B; Pushevski, V; Selim, G; Rambabova Bushljetik, I; Spasovski, G (Macedonian Association of Anatomists, 2020)
Background: Non-compliant dialysis patients are at increased risk of mortality. Compliance and quality of life depends on demographics, education, income, family-support, marital status. Missed dialysis sessions, non-adherence to medications, excessive phosphate levels, inter-dialytic weigh-gain, smoking and non-adherence to medical investigations provide indicators of non-compliance. Aim: Assessing impact of family support on compliance-indicators in dialysis patients. Methods: 134patients were scored for compliance from 0-2; Summary scores were also assessed. 2-year data was obtained. Patients with mean IDWGs ˃4.5% and/or phosphorous level above 1.6mmol/L-scored 1, patients with IDWG/BW >5.7%, Pi 2.0mmol/L-scored 2. Summary scores were also assessed. Quality of life scored with SF-36 questionnaire. Non-adherence was analyzed for predictors in multivariate analysis. Results: Estimated rates of non-compliance varied: medical investigations 63%, phosphorus 33, IDWG 22, therapy 14%, HD treatment 9%. When dietary fluid, medications and treatment regimen were studied, non-compliance rate was 73%, adding adherence to medical investigations rose rate to 87%. Patients with family support above median level (25) were significantly more often men (0.049), diabetic (p=0.014), low socioeconomic status (0.001), married (0.003). Poor family support scored significantly worse in quality of life (56.7326.15vs.39.2324.05, p=0.0001), and overall non-compliance scores 2.041.71vs.2.972.06, p= 0.007). In multivariate analysis non-compliance was predicted best in patients of younger age, low social status, lower family support (=-0.202, p=0.023, =0.220, p=0.036, =-0.175, p=0.019, respectively). Conclusion: Family support is crucial for patients’ compliance to treatment and quality of life. Efforts should be done to meet patients’ needs and help those confronting dialysis burden to improve quality of life.